Enhanced mechanical properties in Cf/LAS composite with yolk-shell structure interface. Issue 14 (November 2022) - Ma, Shishuai; Wang, Chi; Li, Heqi; Li, Tian-tian; Geng, Yongsheng; Ren, He; Xia, Long; Yang, Hua; Zhong, Bo; Xiong, Li; Huang, Xiaoxiao; Wen, Guangwu
Abstract: A new approach to improve the interfacial matching of carbon fiber-reinforced lithium-aluminum-silicon(Cf /LAS) composites is proposed, which is achieved by Ni nanoparticles catalyzing the formation of a tunable graphite layer on the surface of Cf . The interfacial structure between the composites can be effectively improved by tuning parameters such as Ni 2+ content and sintering holding time, and ultimately, the mechanical properties of the composites can be improved. Interestingly, due to the introduction of Ni 2+, a yolk-shell type graphite layer is formed between the Cf and LAS, and the bridging effect of the graphite layer improves interfacial bonding. The highest flexural strength (515 ± 30 MPa) and fracture toughness (14.7 ± 1.6 MPa·m 1/2 ) were obtained. Taking Cf /LAS as an example, the relationship between interfacial matching and mechanical properties of composites is systematically investigated and may provide a new idea for the improvement of mechanical properties of fiber-reinforced composites.